2003
DOI: 10.1002/jbm.b.10055
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion resistance of medical glove materials

Abstract: Due to the increasing demand for nonlatex medical gloves in the health-care community, there is a need to assess the durability of alternative glove materials. This study examines durability characteristics of various glove materials by abrasion resistance testing. Natural rubber latex (latex), polyvinyl chloride (vinyl), acrylonitrile butadiene (nitrile), polychloroprene (neoprene), and a styrene-ethylene/butylene-styrene block copolymer (SEBS) were tested. All test specimens, with the exception of the vinyl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…Polyvinyl chloride gloves have been proposed as a cost-effective and feasible alternative. The problem is that these soft pliable gloves become hard and irregular and develop sharp cutting edges after ingestion [5][6][7][8][9]. In addition, polyvinyl chloride can produce toxic substances.…”
Section: Vinyl Glove Ingestion In Childrenmentioning
confidence: 99%
“…Polyvinyl chloride gloves have been proposed as a cost-effective and feasible alternative. The problem is that these soft pliable gloves become hard and irregular and develop sharp cutting edges after ingestion [5][6][7][8][9]. In addition, polyvinyl chloride can produce toxic substances.…”
Section: Vinyl Glove Ingestion In Childrenmentioning
confidence: 99%
“…In another study where gloves were stressed according to a designated protocol before examining for leakage properties, failure rates were 2.2% for NRL and 1.3% for nitrile gloves, which were again better than for vinyl or copolymer (8.2% for each) [30]. Barrier integrity following an abrasion test demonstrated that NRL gloves were better than vinyl, although not as good as either nitrile or neoprene [31]. …”
Section: Glove Propertiesmentioning
confidence: 99%
“…17. Glove abrasion resistance apparatus (Walsh et al, 2004) www.intechopen.com This device converts the rotary motion of an adjustable-speed, DC gear motor into oscillating linear displacement of a carriage that serves as a translating support for a vertical loading column. The abrader is linearly stroked against a test specimen at a rate that is preset by adjustment of a motor speed control.…”
Section: Abrasion Resistance In Technical Textilesmentioning
confidence: 99%
“…The abrader is linearly stroked against a test specimen at a rate that is preset by adjustment of a motor speed control. Along with displaying the preset number of cycles for a particular test sequence, the system control unit also indicates real-time values of test cycles and cycle rate (Walsh et al, 2004).…”
Section: Abrasion Resistance In Technical Textilesmentioning
confidence: 99%